2020
DOI: 10.1111/jsr.13074
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep pattern, sense of time and digital media use during COVID‐19 lockdown in Italy

Abstract: dress this critical situation and to reduce the spread of the infections, the Italian Prime Minister Giuseppe Conte signed a series of decrees that imposed restrictions on the movement of individuals in the entire national territory from March 10 until May 3 (but these measures are likely to be extended). People are allowed to leave their homes for limited and documented purposes (e.g., shopping for basic necessities and to go to work [if this cannot be done from home]). Several activities have been temporaril… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

145
960
12
39

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 929 publications
(1,220 citation statements)
references
References 15 publications
145
960
12
39
Order By: Relevance
“…Any stressful event, whether related to personal life or caused by natural disasters, precipitates sleep disturbances, particularly among people with greater vulnerability such as the elderly. Surveys in the general population indicate that insomnia, poor sleep, and poor sleep quality are widespread complaints in this pandemic [20]. The observed incidence is similar to that of major crises involving, for example, natural disasters such as earthquakes or floods.…”
Section: Sleep Changes In the Covid-19 Pandemicmentioning
confidence: 82%
“…Any stressful event, whether related to personal life or caused by natural disasters, precipitates sleep disturbances, particularly among people with greater vulnerability such as the elderly. Surveys in the general population indicate that insomnia, poor sleep, and poor sleep quality are widespread complaints in this pandemic [20]. The observed incidence is similar to that of major crises involving, for example, natural disasters such as earthquakes or floods.…”
Section: Sleep Changes In the Covid-19 Pandemicmentioning
confidence: 82%
“…This behavior was also documented in Italy during their COVID-19 stay-at-home orders. Cellini et al (2020) showed that participants increased usage of digital media near bedtime and participants shifted their sleep/wake patterns to a later time during stay-at-home 11 . This "bedtime procrastination" i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic is highly affecting people’s general well-being worldwide ( Cao et al, 2020 ; Wang et al, 2020 ; White and Van Der Boor, 2020 ). Recent literature has shown that the uncertainties about health and work, combined with social distancing and homeschooling connected to the forced lockdown, have had an impact on psychological adjustment, influencing anxiety and depression levels, sleep and eating patterns, and somatic symptomatology ( Ahmed et al, 2020 ; Cellini et al, 2020 ; Fernández-Aranda et al, 2020 ; Huang and Zhao, 2020 ; Tian et al, 2020 ; Zhang et al, 2020 ). Negative emotional responses have been found both in the general adult population and medical care staff, as well as in children and adolescents, especially after the announcement of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%